Antegrade axillary arterial perfusion in 3D endoscopic minimally-invasive mitral valve surgery - Petersen, Johannes; Naito, Shiho; Kloth, Benjamin; Pecha, Simon; Zipfel, Svante; Alassar, Yousuf; Detter, Christian; Conradi, Lenard; Reichenspurner, Hermann; Girdauskas, Evaldas (Frontiers in Cardiovascular Medicine, 2022)
Background Minimally-invasive (MIS) mitral valve surgery has become standard therapy in many cardiac surgery centers. While femoral arterial perfusion is the preferred cannulation strategy in MIS mitral valve surgery, retrograde arterial perfusion is known to be associated with an increased risk for cerebral atheroembolism, particularly in atherosclerosis patients. Therefore, antegrade perfusion may be beneficial in such cases. This analysis aimed to compare outcomes of antegrade axillary vs. retrograde femoral perfusion in the MIS mitral valve surgery. Methods This analysis includes 50 consecutive patients who underwent MIS between 2016 and 2020 using arterial cannulation of right axillary artery (Group A) due to severe aortic arteriosclerosis. Perioperative outcomes of the study group were compared with a historical control group of retrograde femoral perfusion (Group F) which was adjusted for age and gender (n=50). Primary endpoint of the study was in-hospital mortality and perioperative cerebrovascular events. Results Patients in group A had a significantly higher perioperative risk as compared to Group F (EuroSCORE II: 3.9±2.5 vs. 1.6±1.5 p = 0.001; STS-Score: 2.1±1.4 vs. 1.3±0.6; p = 0.023). Cardiopulmonary bypass time (group A: 172±46; group F: 178±51 minutes; p= 0.627) and duration of surgery (group A: 260±65; group F: 257±69 minutes; p= 0.870) were similar. However, aortic cross clamp time was significantly shorter in group A as compared to group F (86±20 vs. 111±29 minutes, p < 0.001). There was no perioperative stroke in either groups. In-hospital mortality was similar in both groups (group A: 1 patient; group F: 0 patients; p = 0.289). In group A, one patient required central aortic repair due to intraoperative aortic dissection. No further cardiovascular events occurred in Group A patients. Conclusion Selective use of antegrade axillary artery perfusion in patients with systemic atherosclerosis shows similar in-hospital outcomes as compared to lower risk patients undergoing retrograde femoral perfusion. Patients with higher perioperative risk and severe atherosclerosis can be safely treated via the minimally invasive approach with antegrade axillary perfusion.